2010
DOI: 10.3348/kjr.2010.11.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Diagnosis of Either an Occult or Missed Fracture of an Extremity in Pediatric-Aged Children

Abstract: ObjectiveTo report and assess the usefulness of ultrasound (US) findings for occult fractures of growing bones.Materials and MethodsFor six years, US scans were performed in children younger than 15 years who were referred with trauma-related local pain and swelling of the extremities. As a routine US examination, the soft tissue, bones, and adjacent joints were examined in the area of discomfort, in addition to the asymptomatic contralateral extremity for comparison. Twenty-five occult fractures in 25 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 23 publications
0
46
0
1
Order By: Relevance
“…Recent studies have suggested the diagnostic superiority of US in radiographically occult fractures. 52,53 Plain radiographs may be inadequate with buckle and Salter Harris I fractures in the pediatric population, as demonstrated by Patel et al 41 and Chen et al 34 In the study by Patel et al two patients were found to have buckle fractures detected by US not seen on the initial x-ray, which were confirmed by callous formation at a later date. The study by Chen et al found three patients suggestive of distal radial fracture by effusion on US with normal x-rays diagnosed as Salter Harris I fracture on repeat clinical examination.…”
Section: Implications For Future Researchmentioning
confidence: 95%
“…Recent studies have suggested the diagnostic superiority of US in radiographically occult fractures. 52,53 Plain radiographs may be inadequate with buckle and Salter Harris I fractures in the pediatric population, as demonstrated by Patel et al 41 and Chen et al 34 In the study by Patel et al two patients were found to have buckle fractures detected by US not seen on the initial x-ray, which were confirmed by callous formation at a later date. The study by Chen et al found three patients suggestive of distal radial fracture by effusion on US with normal x-rays diagnosed as Salter Harris I fracture on repeat clinical examination.…”
Section: Implications For Future Researchmentioning
confidence: 95%
“…Recent research has revealed that ultrasound has superior sensitivity to radiography in certain types of fractures, 33 and it has been shown to detect nondisplaced fractures as small as 1 mm. 34 Our study included a case of a 16-year-old male who presented with a boggy frontal scalp hematoma after an assault.…”
Section: Figurementioning
confidence: 99%
“…[9,14] Injuries to the physis can occur at any age before physeal closure, but are most common during periods of rapid skeletal growth. Although problems after injury to the physis are uncommon, missed injuries to this area can lead to premature closure with resultant focal bone growth arrest.…”
Section: Childmentioning
confidence: 99%
“…Knowledge of these patterns is key for the emergency physician to avoid this potential orthopedic pitfall. [9,34,35] The incidence of pediatric cases of occult fractures occurs in about 2-18% of reviewed cases. [3,9] In our study occult fractures were detected using CT in 12 (6.6%) of the children.…”
Section: Childmentioning
confidence: 99%